Hybrid ARQ with selective combining for fading channels. - Qinqing Zhang (IEEE Journal on selected areas in communications)
We propose and analyze a hybrid automatic repeat request (ARQ) with a selective combining scheme using rate-compatible punctured convolutional (RCPC) codes for fading channels. A finite-state Markov channel model is used to represent the Rayleigh fading channels. We show that the hybrid ARQ with selective combining yields better performance than the generalized type-II ARQ scheme for fading channels. Furthermore, simulation results of real-time video time division multiple access (TDMA) transmission system are given. Better video quality can be obtained by our proposed scheme, with a bounded delay. Analytical results of throughput and packet error rate (PER) are compared to the simulated results. Our analysis based on a finite-state Markov channel model, is shown to give good agreement with simulations